DEFECT ANALYSIS ON SMOOTHMILL FACILITY USING PRIORITYCOST FAILURE MODE, EFFECT, AND CRITICALITY ANALYSIS (PCFMECA) METHODSATPT. EBAKO NUSANTARA - Arfan Bakhtiar, Bambang Purwanggono Ranintia Adhi Citra Pramesti (USIM, THAMKAM, KHON KAEN, UMY, 2016)
FMEA (Failure Mode and Effects Analysis) is a method to identify potential failure modes of a process or product, which has been used since 1950 inside an aviation control system. To implement more efficient improvement of FMEA, criticality analysis was then added into every failure mode, termed Failure Mode, Effects, and Criticality Analysis (FMECA). However, those methods are yet to integrate cost variable, which are essential in the rapid growth of manufacturing industries. Priority-Cost FMECA (PC-FMECA) emerged to reach such objective. PT. Ebako Nusantara is a high-end furniture manufacturing with several steps of production. Interview with QC Department and Event Defect Finding Data in October 2015 portrayed SmoothmillFacility as the area responsible for the largest event defect total in October 2015, which are 32,78%. This research is done to investigate the failures occurring during production so that event defect could be reduced, if not eliminated. This research uses PC-FMECA method, which takes profitability of action into account. In this method, the New RPN is calculated with the adoption of AHP technique, where profitability values are then formulated. Criticality matrices are drawn using priority-profitability diagram to formulate priority of failure. Upon this method, the recommendations are then customized to not exceed the budget of the company. Keywords: FMEA, PC-FMECA, event defect, New RPN, profitability